(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
“Legal and legal foundations of the formation of students as socially active persons and their promotion” political and legal knowledge and culture of the socially active shazs model, covering the content and essence of the components, clarified some social causes and conditions of the student’s inappropriate behavior and issues of its promotion